Climate change adaptation, gender, and mainstreaming: The role of gender in Fiji's relocation initiative - Bertana, Amanda; Blanton, Natalie (Climate and Development, 2022)
Climate change has elucidated already existing gender inequalities associated with unequal access to resources, decision-making processes, and higher exposure to environmental shocks and stressors. Growing acknowledgment of the gender-differentiated implications of climate change in recent years has placed gender equality as a focal point in international discourses on climate change adaptation. The policy perspective of gender equality is universalized, but how it transcribes in local climate change adaptation projects remains elusive. Using the relocation of Vunidogoloa, Fiji, this article explores the tension and compatibility between the way gender equality is discussed and how it is implemented in climate change adaptation projects. © 2022 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2010-2019; changements climatiques; discipline; environnement; ethnographie; fidji; océanie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; sécurité alimentaire; thématiques

Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Coronavirus, domestic labour and care: Gendered roles locked down - Craig, Lyn (Journal of Sociology, 2020)
The Covid-19 pandemic turned daily lives upside down. Lockdowns and physical distancing meant hundreds of thousands of people switched to working from home, significantly blurring the temporal and spatial boundaries between paid work, domestic labour and caring for others. This article explores gender relations, and the division of employment, domestic labour and care, drawing on early results from an online survey, Work and Care in the Time of Covid-19, carried out between 7 May and 4 June 2020.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; australie; care; covid-19; discipline; division sexuelle du travail; océanie; pandémie; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail de reproduction; travail invisible

A visual analysis of gender bias in contemporary anatomy textbooks - Parker, Rhiannon; Larkin, Theresa; Cockburn, Jon (Social Science & Medicine, 2017)
Les recherches empiriques ont établi un lien entre les préjugés sexistes dans l’enseignement médical et les attitudes et comportements négatifs des prestataires de soins de santé. Pourtant, cela fait plus de 20 ans que les recherches n’ont pas examiné dans quelle mesure les femmes et les hommes sont représentés de manière égale dans les manuels d’anatomie . En outre, les recherches antérieures n’ont pas exploré au-delà de la quantité de représentation pour examiner également les stéréotypes visuels de genre et, à la lumière des avancées théoriques dans le domaine de la recherche intersectionnelle, la relation entre les représentations du genre et les représentations de l’ethnicité, du type de corps, de la santé et de l’âge. Cette étude visait à déterminer l’existence et la représentation des préjugés sexistes dans les principaux manuels d’anatomie utilisés dans les écoles de médecine australiennes. Une analyse systématique du contenu visuel a été menée sur 6044 images dans lesquelles le sexe/genre pouvait être identifié, provenant de 17 principaux manuels d’anatomie publiés entre 2008 et 2013. Une analyse de contenu plus approfondie a été réalisée sur les 521 images narratives, qui représentent une histoire en cours, trouvées dans les mêmes manuels. Les résultats indiquent que la représentation du genre dans les images des manuels d’anatomie reste majoritairement masculine, sauf dans les sections spécifiques au sexe. En outre, d’autres formes de biais ont été constatées dans : la visualisation d’émotions, de rôles et de contextes stéréotypés en fonction du sexe ; le manque de diversité ethnique, d’âge et de type corporel ; et dans l’adhésion presque totale à une conception binaire sexe/genre. Malgré une attention accrue portée aux questions de genre en médecine, la représentation visuelle du genre dans les programmes médicaux continue d’être biaisée. La construction biaisée du genre dans les manuels d’anatomie conçus pour l’enseignement médical fournit aux futurs prestataires de soins de santé des informations inadéquates et irréalistes sur les patients.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; australie; corps; discous dominant; intersectionnalité; livres d'anatomie; océanie; projet charge mentale; périodes historiques; racisme; représentation des corps; régions géographiques; santé; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques